Peningkatan Kompetensi Supervisi Kepala Sekolah Melalui Supervisi Kelompok di Sekolah Dasar - Kusmanto, Benedictus (Muhammadiyah University Press, 2016)
The research is aimed to: 1) describe the process of managerial supervision using group technique to improve the principalsâ supervisory competence; and 2) imrove the principalsâ supervisory competence at Gugus II Bima UPTD Dikpora Kecamatan Serengan of Surakarta academic year 2012/2013 through managerial supervision using group technique.The type of the research is an action research. The research was done at Gugus II Bima UPTD Dikpora Kecamatan Serengan of Surakarta. The subjects of the research were 6 principals at Gugus II Bima UPTD Dikpora Kecamatan Serengan of Surakarta. The data collecting techniques were done using observation,Â interviewÂ andÂ documentÂ techniques.Â TheÂ dataÂ analysisÂ technique was done using Kemmis and Taggart model.The research concludes that: 1) the managerial supervision processes were done in three stages, namely: initial stage, observation stage, and feed-back stage; and 2) the managerial supervision using group technique is effective in improving the principalsâ supervisory competence at Gugus II Bima UPTD Dikpora Kecamatan Serengan of Surakarta academic year2012/2013. It is demonstrated by the score improvement in each cycles.